A Review of Quality Control in Food Safety for Fast-Moving Consumer Goods Products - Mahindrakar, Nikita (Digital Repository of Theses, 2025)
The health and confidence of their customers are at stake; thus, fast-moving consumer goods firms have the responsibility to ensure the safety of the food they sell. This analysis focuses on the safety and quality control of fast-moving consumer goods. The concerns associated with fast-moving consumer goods' food safety and quality control are discussed first in this study. The HACCP and GMP systems, which are used to regulate quality control, are analysed next. The evaluation takes into account the selection of raw materials for quality control, as well as manufacturing, packing, storage, and distribution. fast-moving consumer goods products are protected from microbiological, chemical, and physical contamination thanks to quality control. The capacity to trace products and maintain accurate records are both helpful in reducing the time it takes to issue product recalls. Testing that is both quick and based on DNA, as well as remote monitoring systems, are additional topics of discussion. The process of quality control is included in every stage of the supply chain, from the management of suppliers to the aftermarket monitoring of products. When it comes to establishing quality control methods, fast-moving consumer goods firms confront challenges such as financial limits, the complexity of global supply chains, and various regulatory requirements. The use of risk assessment tools, continual training, and supplier cooperation are all being investigated as potential solutions to these problems. The examination is brought to a close with a synopsis of fast-moving consumer goods food safety quality control, with an emphasis on the need for continual vigilance and the capacity to adjust to emerging threats. It emphasizes continuous improvement, data-driven decision-making, and proactive quality control to protect the health of consumers and the reputation of the business. This assessment provides fast-moving consumer goods firms, regulators, and other interested parties with important insights into the quality control of food safety for fast-moving consumer goods.